2012
DOI: 10.1111/j.1365-2656.2012.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Biases in comparative analyses of extinction risk: mind the gap

Abstract: 1. Comparative analyses are used to address the key question of what makes a species more prone to extinction by exploring the links between vulnerability and intrinsic species' traits and/or extrinsic factors. This approach requires comprehensive species data but information is rarely available for all species of interest. As a result comparative analyses often rely on subsets of relatively few species that are assumed to be representative samples of the overall studied group. 2. Our study challenges this ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 46 publications
(66 reference statements)
0
129
1
Order By: Relevance
“…Future work is necessary to determine whether our results can be generalized to other taxonomic groups and to understand how different processes leading to observed variation influence population dynamics. To achieve this goal, it is critical to assemble data sets that capture intraspecific variation-if possible at the population level-instead of providing only mean trait descriptors, while trying to avoid taxonomic and spatial biases that can influence results from comparative analyses (González-Suárez et al 2012). In addition, future research should aim to identify the mechanisms responsible for the observed patterns, differentiating genetic and phenotypic sources of variation, since they may play different roles in population dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future work is necessary to determine whether our results can be generalized to other taxonomic groups and to understand how different processes leading to observed variation influence population dynamics. To achieve this goal, it is critical to assemble data sets that capture intraspecific variation-if possible at the population level-instead of providing only mean trait descriptors, while trying to avoid taxonomic and spatial biases that can influence results from comparative analyses (González-Suárez et al 2012). In addition, future research should aim to identify the mechanisms responsible for the observed patterns, differentiating genetic and phenotypic sources of variation, since they may play different roles in population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, missing trait data are prevalent in our database (table 1) and present a challenge for the analyses (González-Suárez et al 2012). Although imputation techniques may be used to fill missing data, we did not follow this approach because missing values are not missing at random in these data (González-Suárez et al 2012) and because of the complexity of imputing intraspecific variation.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…PanTHERIA provides median estimates for 30 variables describing morphology, development, reproduction, ecology and spatial data for 5415 mammals, but data are not available for all species and some traits are particularly data-poor with a pattern of data not missing at random (González-Suárez et al 2012). To address some of these limitations we only considered traits with data for .1000 species, among which we selected five variables that describe the reproductive and life-cycle speed and one describing diet breadth (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Gaps and heterogeneity in the geographical and taxonomical coverage of existing information on biodiversity have also been recognized as critical problems in other global efforts to assess the status of global biodiversity [5,8,9]. A recent study demonstrated that existing biases in available information can lead to inaccurate inferences in ecological studies [10].…”
Section: Introductionmentioning
confidence: 99%